Determination of Diet Composition of Genus Barbodes (Family: Cyprinidae) at Selected Streams in Kuching and Kota Samarahan Division, Sarawak - Radin Azreena, Radin Shahrom (Universiti Malaysia Sarawak (UNIMAS), 2017)
The Barbodes is a genus of freshwater fish from family Cyprinidae. Earlier studies of dietary of the freshwater fish stated that fish from this genus either feeds on vegetation or invertebrates or both. Despite these studies, there are still gaps in knowledge regarding the specialisation in diet of genus Barbodes, whether the different speciesofthis genus have different dietary composition influenced by their habitat. The aim of this research is to determine the diet of five species of genus Barbodes through stomach content analysis and to determine the dietary composition offive species of genus Barbodes. This study was conducted at selected freshwater streams in Kuching and Kota Samarahan Division including Kubah National Park, Matang Wildlife Centre, UNIMAS, Mile 7 and Kampung Benuk. A total of 114 specimens comprising of five species namely (i)Barbodes seale; (n=44), (ii) Barbodes binotatus (n=3), (iii) Barbodes lateristiga (n=l1), (iv) Barbodes banksi (n=37) and (v) Barbodes kuchingensis (n=19) were analysed for stomach content analysis. Stomach content was obtained" through dissection. The stomach content was observed under stereo microscope and sorted according to its taxonomic group of food. Seventeen types of diet preferences were recorded. The data revealed two types of diet which is more preferable by this genus which are Macrophyte Type A and Macrophyte Type C.